Penalaran Matematika Siswa SMP pada Soal Cerita - Andi Kurnia Riski Sanneng; Rohati Rohati; Duano Sapta Nusantara (SJME (Supremum Journal of Mathematics Education), 2026)
This study aimed to describe the mathematical reasoning profiles of eighth-grade students in solving linear equations in one variable (LEOV) word problems. A descriptive qualitative approach was employed as a preliminary investigation before the development of an instructional intervention. The participants were 27 eighth-grade students from a public junior high school in Jambi City who had previously studied LEOV. Data were collected through two essay-based word problems developed according to five mathematical reasoning indicators: formulating hypotheses, performing mathematical manipulations, constructing proofs, drawing conclusions, and verifying the validity of arguments. The test items were reviewed by a mathematics education lecturer and complemented by semi-structured interviews with six purposively selected students representing high, moderate, and low reasoning categories. Data were analyzed through data reduction, data display, conclusion drawing, descriptive statistics, and triangulation of written responses, interview results, and supporting documentation. The findings revealed that students’ mathematical reasoning ability was generally low, with an average score of 9.19 out of 40. Of the participants, 3.70% were classified in the high category, 14.81% in the moderate category, and 81.48% in the low category. Formulating hypotheses showed the highest achievement at 28.24%, whereas verifying the validity of arguments was the weakest indicator at 9.72%. High-ability students demonstrated relatively systematic and reflective reasoning, while moderate- and low-ability students experienced difficulties in constructing mathematical models, providing logical justification, drawing context-appropriate conclusions, and checking their solutions. These difficulties were particularly associated with students’ limited ability to visualize the situations described in word problems. The findings highlight the need for visual, contextual, and step-by-step learning activities that strengthen mathematical modeling, argumentation, verification, and students’ confidence in solving LEOV word problems.